МОДЕЛЮВАННЯ ЕЛЕКТРОГІДРОДИНАМІЧНИХ ПРОЦЕСІВ У ВІДБИВНІЙ ПЕЧІ ДЛЯ АЛЮМІНІЮ З ЕЛЕКТРОВИХРОВОЮ КАМЕРОЮ ІЗ УРАХУВАННЯМ ДЕФОРМАЦІЇ ВІЛЬНОЇ ПОВЕРХНІ РІДКОГО МЕТАЛУ - Бондар, О.І.; Гориславець, Ю.М.; Пеньковий, Т.О. (Інститут електродинаміки НАН України, Київ, 2026)
A scheme of a reverberatory furnace for melting aluminum waste with a cylindrical electrovortex chamber, in which a vortex (rotating) flow of liquid metal is created using a curve inductor, is presented. This chamber is connected to the melting bath of the furnace by two channels and performs two functions: it stirs the molten metal in the furnace bath and immerses crushed metal scrap into the melt to protect the metal from oxidation with its subsequent transportation to the melting bath. For such a system, a mathematical model has been formulated to study electromagnetic and hydrodynamic processes in it, taking into account the deformation of the free surface (meniscus) of the liquid metal. The model consists of two parts - systems of differential equations that describe the specified processes. The deformation of the free surface was determined by the moving grid method. The study was conducted for different values of the height of the metal in the furnace bath, which varied from the initial value of 0.2 m to the full height of the bath of 0.5 m, which simulated the process of metal deposition in the furnace during operation. Two options for the location of the inductor along the height of the vortex chamber were considered: one - in its lower part, and the second - in the middle relative to the height of the metal of the fully deposited furnace bath. As a result of the simulation, the velocity distributions of the liquid metal in the furnace bath and the vortex chamber were obtained, the deformation of the upper free surface of the metal in the chamber and the average level of metal in it relative to the level of metal in the melting bath were determined. For different fillings of the furnace bath, the trajectories of the movement of the liquid metal in the electrovortex chamber were determined. References 10, figures 8.